OP0191 The Fecal Microbiota of Rheumatoid Arthritis Patients Differs from that of Healthy Volunteers and is Considerably Altered by Treatment with Biologics. (23rd January 2014) - Maeda, Y.; Matsushita, M.; Yura, A.; Teshigawara, S.; Katayama, M.; Yoshimura, M.; Watanabe, A.; Tanaka, E.; Tsuji, S.; Kitatobe, A.; Harada, Y.; Ohshima, S.; et al.
Abstract : Background: New insights from DNA sequence-based analyses of gut microbial communities and the renewed interest in mucosal immunology suggest that the microbiome is an important environmental factor influencing autoimmune disease manifestations. Objectives: To investigate the fecal microbiota of rheumatoid arthritis (RA) patients and healthy volunteers (HVs), we used the Yakult Intestinal Flora-SCAN (YIF-SCAN ® ), based on reverse transcription–quantitative polymerase chain reaction, with primers specific for target bacterial rRNA. We also investigated whether the fecal microbiota changed in RA patients due to biologic (Bio) treatment. Methods: Fecal samples were collected from 55 RA patients and 77 HVs in NHO Osaka Minami Medical Center during 2011–2012. YIF-SCAN® was performed to quantify the bacterial count with 16S or 23S rRNA-targeted group-specific primers. 25 RA patients were re-examined after they underwent Bio treatment (tocilizumab, 10; infliximab, 9; etanercept, 3; adalimumab, 1; abatacept, 2) for 6 mo. Patients who had received antibiotic therapy were excluded. Results: The mean age was 57.8 ± 14.5 and 36.3 ± 10.7 years; mean body weight, 54.5 ± 10.0 and 57.0 ± 9.0 kg; and the proportion of women, 72.7% and 90.9%, for the RA patients and HVs, respectively. From the facultative anaerobic groups, the total population levels of Lactobacillus (especially the Lactobacillus gasseri, L. reuteri, and L. fermentum subgroups) and Enterococcus, Enterobacteriaceae were significantly higher in RA. These results support those of our 2012 study [1]. The background of the 25 RA patients reanalyzed after treatment is shown in Table 1 . The DAS28CRP was 4.1 ± 1.1 at baseline and 2.5 ± 1.1 at 6 mo. 12 patients (48%)achieved remission (DAS28CRP < 2.3) at 6 mo. The total bacterial count and total population levels of the Clostridium. coccoides group, Bifidobacterium, and the L. gasseri and L. plantarum subgroups significantly decreased at 6 mo (Table 2 ). Conclusions: We confirmed the difference in the fecal microbiota of RA patients and HVs. Bio treatment considerably reduced commensal bacteria in RA patients. To our knowledge, this is the first study describing changes in fecal microbiota due to Bio treatment. Further studies are required to elucidate the clinical significance of these results. References: Y.maeda, et al. Ann Rheum Dis 2012;71(Suppl3):496 Disclosure of Interest: None Declared